2018
DOI: 10.1371/journal.pone.0201030
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of interacting with Spt6 (Iws1) causes early embryonic lethality

Abstract: IWS1 is an RNA-polymerase II (RNAPII)-associated transcription elongation factor whose biological functions are poorly characterized. To shed some light on the function of this protein at the organismal level, we performed a systematic tissue analysis of its expression and generated Iws1-deficient mice. A thorough immunohistochemical characterization shows that IWS1 protein is present in the nucleus of all cells in most of the examined tissues, with few notable exceptions. We also report that ablation of Iws1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…After submission of our manuscript to this journal, a paper was published indicating the crucial role of Iws1 in mouse preimplantation embryo development 55 , supporting our findings in this study.…”
Section: Discussionsupporting
confidence: 87%
“…After submission of our manuscript to this journal, a paper was published indicating the crucial role of Iws1 in mouse preimplantation embryo development 55 , supporting our findings in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Mutation of SPT6 facilitates chromatin relaxation in specific genomic regions, which impacts the regulation of transcription, genomic stability and hyperrecombination 23 , 43 48 . Previous reports implicated SPT6’s chromatin remodeling activities to regulate zebrafish myogenesis 49 and mouse embryogenesis 50 . Here, we describe a pro-tumorigenic role for SPT6 in GBM and provide a mechanistic insight into its role in one of the deadliest of solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, recent studies showed that Spn1 is required for normal transcript levels in both yeast and mammalian cells (REIM et al 2020;CERMAKOVA et al 2021), as well as for mRNA splicing and histone modifications (YOH et al 2007;YOH et al 2008;REIM et al 2020). Furthermore, in mammalian cells, Spn1 is essential for embryonic development and cell proliferation (LIU et al 2007;ORLACCHIO et al 2018;OQANI et al 2019), and it has been implicated in cancer (DAVOLI et al 2013;SANIDAS et al 2014).…”
Section: Introductionmentioning
confidence: 77%